STRENGTHENING EDUCATIONAL SYSTEMS THROUGH DATA INTEGRITY: INSIGHTS FROM THE MINISTRY OF EDUCATION MALAYSIA’S DATA CENTER - Azlin Ramli; Mohamad Yusof Darus; Othman Talib; Azliza Yacob (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
It examines the factors that affect data integrity in the Data Center of the Ministry of Education Malaysia (KPM) and analyzes the effectiveness of existing security measures. By ensuring data integrity, educational systems can be strengthened, leading to more reliable and effective decision-making processes. This, in turn, supports the overall goal of enhancing educational outcomes. This study uses a qualitative research approach by interviewing five civil servants related to the management of government data centers. The findings of the study show that there are several weaknesses in the management of cyber security in data centers, including lack of training and security awareness, insufficient monitoring and periodic audits, as well as lack of support and commitment from superiors. In addition, this study also found that the existing cyber security policy is not strict and clear enough, and investment in security technology is still low. Based on these findings, the ENSTEK Data Center Data Security and Integrity model has been developed to overcome these weaknesses. This model contains the components of security training and awareness, regular monitoring and audits, investment in security technology, strict and clear cyber security policies, and support and commitment from the top. This model is expected to improve the security and integrity of data in government data centers as well as provide important guidance for further research in the field of cyber security.